Ability of medication correction by means neurotropic drugs for disorders in metabolical cycle of neurotoxic transmitter — glutamat in retina during experimental glaucoma (Ukrainian Journal of Ophthalmology, 2026)
The aim of this scientific work is to study the abilities of medical correction of violations in metabolic cycle of glutamine acid in the retina of 53 rabbits with experimental glaucoma using enzymatic analysis. Experimental animals were divided on 3 groups: intact (control group), research group with glaucoma, research group with glaucoma treated by neuroprotectors. Supervision was made at 3 weeks 1st term, 5–6 weeks 2nd term, 10 weeks 3rd term. We used Mema in dose 5 mg/kg per day, Neurodar 100 mg/kg per day everyday through all term of experiment. Results. Еhe concentration of glutamate in the retina of animals was increased to 14.90±0.75 mkmol/g (120.0 % of normal level 12.42±0.60 mkmol/g) at 1st term of glaucoma process development, 19.87±0.80 mkmol/g (160.0 %) and 21.76±0.70 mkmol/g (175.2 %) at 2nd and 3rd terms. Concentration of glutamate with usage of neuroprotectors was 14.28±0.62 mkmol/g (115.0 %) at 1st term, 16.17±0.74 mkmol/g (130.2 %) at 2nd term, 16.77±0.56 mkmol/g (135.0 %) at 3rd term. The positive effect of neuroprotective therapy was also admitted on activity of glutamine synthetase, glutamate oxidase and glutaminase enzyms.
Keywords: glaucoma; glutamate; glutamine; glutamine synthetase; glutamate oxidase; glutaminase; memantine; citicoline